HOW SOCIAL MOVEMENT WORKS IN MUHAMMADIYAH: A CASE STUDY OF AL-KHUZAEMAH MOSQUE - Mahbub Wijaya, Mirza; Budiman, Mamdukh; Firdaus, Nuzulul (Harmoni, 2023)
This study analyzes and explores mosque management from the perspective of grassroots social movements within Muhammadiyah. Through observable phenomena, the author elaborates on the theory of social movements within mosques affiliated with Muhammadiyah. This qualitative descriptive research was conducted at Al-Khuzaemah Grand Mosque in Pekalongan Regency. The study involved six informants, including mosque officials, organizational leaders, and Muhammadiyah sympathizers. Data was collected through observation, interviews, and documentation. Data analysis was conducted using transcendental phenomenological analysis by Van Kaam. The study’s findings indicate that Muhammadiyah members substantially embrace the concept of religious moderation. The social movement within Al-Khuzaemah Mosque begins with a commitment to integrate with the surrounding community, regular religious study gatherings, training for Muhammadiyah cadres, the selection and invitation of external speakers, and consistent adherence to Muhammadiyah’s values in preaching while respecting the religious practices of other groups. As a result, a grassroots social movement emphasizing religious moderation has substantively emerged.